Risk of Seizures after Endovascular Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-analysis - García-Ballestas, Ezequiel (J Epilepsy Res, 2020)
Seizures in aneurysmal subarachnoid haemorrhage (aSAH) have been described secondary to SAH, changes in cortical function, vasospasm and as a result of treatment effects. Seizures are one of the important clinical determinants in neurological outcome of aSAH. Various studies support the notion of less risk of future seizures in endovascular treatment as compared to the microsurgical clipping, yet there is no conclusive evidence in favour or against the seizure occurrence in aSAH patients after endovascular treatment as compared to the microsurgical treatment. To carry out a systematic review and meta-analysis of the risk of seizures after endovascular management (coiling) of ruptured intracranial aneurysms. A literature search was performed in electronic database of PubMed, MEDLINE, Embase, and Scopus from inception to February 2020, using the terms Seizure, Intracranial aneurysms, embolization, with no constraints applied. Data were pooled using a random-effect model, results were abstracted as odds ratios (ORs) and 95% confidence interval (CI), and heterogeneity was reported as Chi-square. Five studies involving 3,077 patients were included in the meta-analysis. After endovascular management of aSAH, seizure risk was increased by a worse clinical severity (World Federation of Neurosurgery scale or Hunt and Hess) (OR, 3.34; 95% CI, 2.69–4.16; p<0.00001), severe vasospasm (OR, 2.20; 95% CI, 1.67–2.92; p<0.00001), cerebral infarction (OR, 5.19; 95% CI, 3.23–8.35; p<0.00001), and cerebral edema (OR, 1.79; 95% CI, 1.37–2.34; p<0.0000). Worse clinical severity, vasospasm, cerebral infarction and cerebral oedema are significant risk factors for the development of seizures after endovascular intervention in aSAH. The mechanism for this correlation is not clear.